Endplate morphology affects the risk of complications by changing the grafted bony occupancy rate in OLIF patients - Xiao Hu; Haiying Fu; Run Lin; Liyu Ran; Xingrui Peng; Tianhang Xie; Jiancheng Zeng (BMC Musculoskeletal Disorders)
Abstract Background Large contact areas between the grafted bone and the bony endplate (BEP) can optimize the load transmission pattern and decrease the risk of non-union and cage subsidence. The relationship between endplate morphology parameters and complications may stem from the difference in contact sufficiency between the grafted bone and BEP. This study was conducted to verify that changes in endplate morphology affect the risk of complications in patients with oblique lumbar interbody fusion (OLIF) by changing the grafted bony occupancy rate (GBOR). Methods Imaging data of 95 segments of 75 patients who underwent OLIF were collected retrospectively. Endplate morphology parameters, GBOR values, and complications were measured by computational tomography (CT). Results The superior endplate was more concave than the inferior endplate was. The GBOR values in the superior endplate were significantly lower than those in the inferior endplate (coronal and sagittal). The relationship between endplate morphology parameters and GBOR values was significant. The nonfusion rate was significantly higher in the superior endplate. A lower GBOR is an independent predictor of non-union and more severe cage subsidence. Conclusions Changes in endplate morphology affect the risk of cage subsidence and non-union in patients undergoing OLIF by changing the GBOR. Newly designed OLIF cages with larger concave depths on the superior side and different concave angles should be promoted to optimize the match between the grafted bone and the BEP and improve the prognosis of patients with OLIF.